LITERARY AND HISTORICAL REPRESENTATIONS OF BABUR IN UZBEK AND WESTERN NARRATIVES - Kamolova Sadoqat Jabbor qizi (Modern American Journals, 2025)
This article explores the literary and historical representations of the Central Asian ruler Zahiriddin Muhammad Babur in two prominent works: Pirimkul Qodirov’s Yulduzli Tunlar and Harold Lamb’s Babur the Tiger. Through a comparative analysis, the study examines how Babur’s personality, political life, and cultural contributions are depicted in Uzbek and Western literary traditions. While Qodirov presents a deeply introspective and ideologically driven portrait of Babur within a nationalistic and spiritual context, Lamb offers a more action-oriented, heroic narrative tailored to Western historical fiction. The article analyzes the authors’ literary styles, use of historical sources, and their respective cultural lenses. The findings highlight how the same historical figure is reimagined through differing worldviews, thus offering valuable insights into the role of literature in shaping historical memory.
Keywords: Babur, historical fiction, comparative literature, Uzbek literature, Western literature, national identity, cultural perspective